Analysis of the State Administration System in Public Services in the Digital Era - Suci Ramadhani; Giovany Anggasta; Siti Nazira; Ninda Oktaviani Putri; Erinaldi Erinaldi (CV. Civiliza Publishing, 2026)
The development of information and communication technology (ICT) in Indonesia has driven significant transformation in the state administrative system, particularly in the implementation of digital-based public services. This study aims to analyze the role of the state administrative system in improving the quality of public services in the digital era, as well as to identify the challenges and solutions encountered. The method used is a library research approach by examining various relevant scientific literature sources, such as journals, books, official reports, and applicable regulations. The results of the study indicate that the implementation of digital technology through the concept of e-government is able to enhance the effectiveness, efficiency, transparency, and accountability of public services. This is reflected in the increasing use of digital services by the public, along with improvements in a more modern and structured bureaucratic system. However, the implementation of digitalization still faces several challenges, including infrastructure gaps, limited human resource competencies, and the lack of optimal integration between government systems. Therefore, strengthening the state administrative system is necessary through improving the quality of human resources, developing technological infrastructure, and formulating adaptive policies to support the success of digital transformation in public service delivery.